REFORMING COPYRIGHT FOR THE PARTICIPATIVE WEB: BALANCING CREATOR RIGHTS AND USER CREATIVITY - Priancha, Angga (Masalah-Masalah Hukum, 2025)
In the era of the “Participative Web,” copyright regulations are increasingly seen as inadequate for fostering creativity, as they hinder the ability of users to remix and create new works from existing ones. This research explores the limitations and exceptions in Indonesia's copyright law, specifically Law Number 28 of 2014, and their relevance in the digital age. It highlights the growing role of internet users not only as consumers but also as active content creators, blurring the lines between creators and consumers. The study argues that current copyright law, with its rigid structure, restricts freedom of expression and cultural development. It proposes that more flexible copyright limitations and exceptions could facilitate creativity in the participative web, benefiting both creators and users. By comparing Indonesian law with the more flexible "fair use" doctrine in the United States, the research suggests that Indonesia could benefit from adopting a more adaptive approach, including the transformative use doctrine. This would allow for more creativity while balancing the rights of copyright holders. Ultimately, the study calls for a reevaluation of Indonesia’s copyright framework to better align with the needs of the participative web.